MENINGKATKAN AKTIFITAS BELAJAR SISWA MELALUI TUGAS KLIPING - Amiruddin, Amiruddin (Jurnal Analisis Pendidikan Sosial, 2025)
The formulation of this research problem is whether clipping assignment methods can improve the learning activities of grade VII B students of SMPN 1 Anggaberi in the discussion of environmental pollution material. This study aims to determine the influence of clipping assignment methods on students' learning activities in the teaching and learning process. The planned class action research procedure consists of two cycles. The first cycle of grade VIIB students of SMPN 1 Anggaberi, carried out the learning activities of Natural Sciences (IPA) subjects with the discussion of household wastewater pollution material at the first meeting and agricultural wastewater pollution at the second meeting. The second cycle of grade VIIB students of SMPN 1 Anggaberi carried out the learning activities of Natural Sciences (IPA) subjects with the discussion of domestic waste soil pollution material at the first meeting and pollution of agricultural waste soil. Based on the results of research and discussion, it can be concluded that clipping tasks can improve students' learning activities, at the first meeting the results of observation assessment analysis reached a score of 50% within the criteria and increased by 9% at the second meeting with the results of observation assessment analysis reached a score of 59% is in sufficient criteria. In cycle 2 at the first meeting the results of observation assessment analysis reached a value of 75% in good criteria and increased by 12% at the second meeting with the results of observation assessment analysis reached a value of 87% was in good criteria.